Experiments on the Resistance or Pepper Cultivars to Macrophomina phaseolina - Kadlicskó, S.; Kovács, J.; Horváth, J.; Kazinczi, G. (International Journal of Horticultural Science, 2000)
The ashy stern blight of pepper (Capsicum annuum) is often caused by Macrophomina phaseolina. Serious wilt disease occurred between 1994 and 1996 of pepper plants in Hungary. In 1996-98 screening experiments were made on many pepper cultivars. Culture (Knopp) solution experiments, pot experiments, greenhouse and field trials were carried out. We determined the incidence of disease by visual examinations, testing on PDA culture, and light microscope. There were significant differences in susceptibility of cultivars and breeding materials.